2014
DOI: 10.1177/0886260514553635
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychopathy and Exposure to Violence in Rape Myth Acceptance

Abstract: The main aim of the present study was to specify and test a structural model to examine the relationships between four psychopathy dimensions (Interpersonal Manipulation, Callous Affect, Erratic Lifestyle, and Antisocial Behavior), childhood exposure to violence, and rape myth acceptance while controlling for gender, age, sample type (prisoner vs. non-prisoner), and relationship status. Participants were a sample of non-offending adults ( n = 319) recruited from the University of Security in Poznan, and a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 74 publications
(88 reference statements)
4
42
2
4
Order By: Relevance
“…Yet, RMA remained significant in a model that controlled for "perceived norms", which likely overlaps with: "conformity to masculine norms" and "peer support of abuse". Therefore, the variables: psychopathy, and comprehension of sexual consent, might represent the best targets for future research on RMA and sexual violence, especially as there is preliminary evidence elsewhere to suggest an association between RMA and psychopathy (Debowska, Boduszek, Dhingra, Kola, & Meller-Prunska, 2015). This builds on the results of a previous systematic review of the association between RMA and sexual violence behaviours, in which 29 out of 31 cross-sectional studies and 2 out of 3 prospective works established significant associations (Tharp et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…Yet, RMA remained significant in a model that controlled for "perceived norms", which likely overlaps with: "conformity to masculine norms" and "peer support of abuse". Therefore, the variables: psychopathy, and comprehension of sexual consent, might represent the best targets for future research on RMA and sexual violence, especially as there is preliminary evidence elsewhere to suggest an association between RMA and psychopathy (Debowska, Boduszek, Dhingra, Kola, & Meller-Prunska, 2015). This builds on the results of a previous systematic review of the association between RMA and sexual violence behaviours, in which 29 out of 31 cross-sectional studies and 2 out of 3 prospective works established significant associations (Tharp et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…These assessment limitations prevented us from analyzing typological proposals, as others have done (Dixon et al, 2008;Elisha et al, 2010). Recent studies (Debowska, Boduszek, Dhingra, Kola, & Meller-Prunska, 2015;Debowska, Boduszek, & Willmott, in press) also emphasize the weight of childhood exposure to violence in the development of cognitive distortions, and dating sexual violence-supportive attitudes among different types of offenders, including homicide offenders. Although child adjustment and problematic socialization items may include such kind of child abuse, it could be interesting to compare the specific prevalence of victimization in the same type of sample.…”
Section: Discussionmentioning
confidence: 99%
“…Offering tentative support for this, earlier research revealed that childhood exposure to violence can result in cognitive distortions pertaining to rape (Debowska, Boduszek, Dhingra, Kola, & Meller-Prunska, 2014), which can then lead to overtly aggressive behavior (Hersh & Gray-Little, 1998;Lonsway & Fitzgerald, 1994). However, it may also be that certain in-born vulnerabilities in interaction with environmental factors lead to the emergence of criminal behavior (Ertem et al, 2000).…”
Section: Discussionmentioning
confidence: 99%